Influential Article Review - Uncovering the Digital Organization - Weber, Elvira; Rowe, Benny; Adams, Kelly (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines technology. We present insights from a highly influential paper. Here are the highlights from this paper: Increasingly, organizations are assessing their opportunities, developing and delivering products and services, and interacting with customers and other stakeholders digitally. Mobile computing, social media, and big data are the drivers of the future workplace, and these and other digitally based technologies are having large economic and social impacts, including increased competition and collaboration, the disruption of many industries, and pressure being put on organizations to develop new capabilities and transform their cultures. In this article, we provide a conceptual framework for the design of effective digital organizations. Our framework is predicated on the current state of digitization across diverse sectors of the global economy. In the digital world, all activities and transactions leave digital marks, and all actors, things, and places can be reached and affected digitally. As a result, we can design for self-organization rather than using hierarchical mechanisms for control and coordination. Such designs require the strategic and cultural alignment of digital technologies within the organization and externally with stakeholders. We propose that “actor-oriented” principles are at the heart of designing digital organizations and that, if properly applied, can result in a workplace where organization members are highly engaged and productive. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.